2009
DOI: 10.1152/ajplung.90454.2008
|View full text |Cite
|
Sign up to set email alerts
|

Variable stretch pattern enhances surfactant secretion in alveolar type II cells in culture

Abstract: Secretion of pulmonary surfactant that maintains low surface tension within the lung is primarily mediated by mechanical stretching of alveolar epithelial type II (AEII) cells. We have shown that guinea pigs ventilated with random variations in frequency and tidal volume had significantly larger pools of surfactant in the lung than animals ventilated in a monotonous manner. Here, we test the hypothesis that variable stretch patterns imparted on the AEII cells results in enhanced surfactant secretion. AEII cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 34 publications
(53 reference statements)
10
85
2
Order By: Relevance
“…Functional changes to the ASM due to chronic inflammation could potentially inhibit these stretch-induced mechanisms in asthma (18). Alternatively, stretch-activated surfactant release could also be responsible for the bronchoprotective effect of the DI (2,35,63). Our group has also provided some evidence that prohibition of DIs in healthy subjects might simply cause atelectasis, which amplifies reactivity (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional changes to the ASM due to chronic inflammation could potentially inhibit these stretch-induced mechanisms in asthma (18). Alternatively, stretch-activated surfactant release could also be responsible for the bronchoprotective effect of the DI (2,35,63). Our group has also provided some evidence that prohibition of DIs in healthy subjects might simply cause atelectasis, which amplifies reactivity (6).…”
Section: Discussionmentioning
confidence: 99%
“…In protocol 1, it was found that Ptm oscillation from 5-20 cmH 2 O results in significant dilation (36% recovery). In protocol 2, airways were either exposed to large Ptm oscillations before and during constriction (Pre ϩ Post) or only following constriction against a static load (Post Only).…”
Section: Protocol 2: Bronchodilation and Bronchoprotection Of Large Pmentioning
confidence: 99%
“…30 Additionally, distension favors expression of the type I alveolar epithelial cell phenotype, the cells most important for gas exchange in the lung, 31 while variable stretch can increase surfactant secretion by type II alveolar epithelial cells. 32 In our system, ventilation with culture medium may also confer benefits with respect to nutrient and oxygen transport. This may have played a role in the observed EMT as physiological stress and hypoxia may be involved in inducing EMT.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the variability of the breathing pattern itself has also been found to upregulate surfactant secretion (18), which may have a significant impact on how patients will be mechanically ventilated in the future (19). Macroscopic complexity in physiological variables, such as mechanical forces of tidal volume or blood pressure acting on cells (20), can regulate normal cell function.…”
Section: How Does Complexity Arise In the Respiratory System?mentioning
confidence: 99%